Impact of Foreign Direct Investment on the Economic Growth of Nepal - Balami, Sangita; Dhakal, Hem Chandra; Chalise, Dhan Raj; Pradhan, Bijay Lal (Morgan Journal of Interdisciplinary Research Studies, 2024)
The study investigates the factors influencing foreign direct investment (FDI) and its sectoral distribution in the Nepalese economy, specifically examining the relationship and impact of FDI on sectors such as minerals, manufacturing, construction, energy, and services over a ten-year period from 2011/12 to 2020/21. Descriptive and correlational research design was employed in the annual time series data. The major findings reveal a positive correlation (correlation co-efficient of 0.668) between FDI and Gross Domestic Product (GDP), signifying a significant relationship. The study concludes that FDI has a substantial impact on Nepal’s GDP. Additionally, sectoral FDI investments, including minerals, construction, energy, manufacturing, and services, also positively influence the country’s GDP. The study suggests that despite Nepal’s untapped FDI potential, implementation challenges, lengthy approval processes, and a service sector bias among investors hinder optimal exploitation of investment opportunities in other sectors with higher productivity.